A Dual‐Ligand Porous Coordination Polymer Chemiresistor with Modulated Conductivity and Porosity. (22nd November 2019) - Yao, Ming‐Shui; Zheng, Jia‐Jia; Wu, Ai‐Qian; Xu, Gang; Nagarkar, Sanjog S.; Zhang, Gen; Tsujimoto, Masahiko; Sakaki, Shigeyoshi; Horike, Satoshi; Otake, Kenichi; Kitagawa, Susumu
Abstract: Single‐ligand‐based electronically conductive porous coordination polymers/metal–organic frameworks (EC‐PCPs/MOFs) fail to meet the requirements of numerous electronic applications owing to their limited tunability in terms of both conductivity and topology. In this study, a new 2D π‐conjugated EC‐MOF containing copper units with mixed trigonal ligands was developed: Cu3 (HHTP)(THQ) (HHTP=2, 3, 6, 7, 10, 11‐hexahydrotriphenylene, THQ=tetrahydroxy‐1, 4‐quinone). The modulated conductivity ( σ ≈2.53×10 −5  S cm −1 with an activation energy of 0.30 eV) and high porosity (ca. 441.2 m 2  g −1 ) of the Cu3 (HHTP)(THQ) semiconductive nanowires provided an appropriate resistance baseline and highly accessible areas for the development of an excellent chemiresistive gas sensor. Abstract : Macht Sinn : Da zwei Liganden mehr Möglichkeiten als einer bieten, die Leitfähigkeit und Topologie eines MOF zu beeinflussen, wurde ein 2D‐π‐konjugiertes kupferbasiertes elektronisch leitfähiges MOF mit zwei verschiedenen trigonalen organischen Liganden entwickelt. Die resultierenden Nanodrähte zeigten niedrige Leitfähigkeit und sehr zugängliche Oberflächen, was zu hervorragenden chemiresistiven Sensoreigenschaften bei Raumtemperatur führte.